2018
DOI: 10.1088/1751-8121/aad025
|View full text |Cite
|
Sign up to set email alerts
|

Microreversibility, nonequilibrium current fluctuations, and response theory

Abstract: Microreversibility rules the fluctuations of the currents flowing across open systems in nonequilibrium (or equilibrium) steady states. As a consequence, the statistical cumulants of the currents and their response coefficients at arbitrary orders in the deviations from equilibrium obey time-reversal symmetry relations. It is shown that these relations allow us to systematically reduce the amount of independent quantities that need to be measured experimentally or computed theoretically in order to fully chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(77 citation statements)
references
References 52 publications
(278 reference statements)
6
71
0
Order By: Relevance
“…We have also shown that, as a corollary of the fluctuation theorem for the currents, nonlinear transport generalizations of the fluctuation-dissipation and Onsager reciprocal relations are satisfied in the transistor. In particular, we have verified in detail that the second-order nonlinear response coefficients of the currents are related to the first-order responses of the diffusivities, as predicted by theory [11,12,14].…”
Section: Discussionsupporting
confidence: 66%
“…We have also shown that, as a corollary of the fluctuation theorem for the currents, nonlinear transport generalizations of the fluctuation-dissipation and Onsager reciprocal relations are satisfied in the transistor. In particular, we have verified in detail that the second-order nonlinear response coefficients of the currents are related to the first-order responses of the diffusivities, as predicted by theory [11,12,14].…”
Section: Discussionsupporting
confidence: 66%
“…A surprising aspect of our recent works [33,34] has been the use of Euler's polynomials within our mathematical analysis of a fluctuation relation of the form (1), both in the absence [33] and the presence [34] of a magnetic field. In particular, we showed in [34] that the fluctuation relation constrains about half of the (symmetric and antisymmetric parts of the) cumulants and their responses to the affinities.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we first treat in subsection 5.1 the non-trivial case of the antisymmetric relations (48). We then apply in subsection 5.2 the known results of [8,33] to the symmetric relations (47).…”
Section: Independent Quantitiesmentioning
confidence: 99%
“…In addition, we explicitly write the remaining dependent quantities as linear combinations of the independent ones, the coefficients of which being related to Euler polynomials. The main outcome of our work is thus to generalize the findings of [8,33], where no magnetic field is considered, to the case of a nonzero magnetic field. This paper begins with a concise discussion of FR in section 2, before we introduce the statistical cumulants and their responses to the nonequilibrium constraints in section 3.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation